"No strings attached": A qualitative exploration of gay and bisexual men's motivations for and attitudes toward engaging in casual sex while on vacation. Issue 4 (2nd October 2019) - Parrish, Candace; Winkler, Rowena; Seal, David Wyatt; Benotsch, Eric G.; Pinkerton, Steven D.; Redmann, Jean; Fegley, Josh; Seeley, Salvatore; Traylor, Derrick L.; Green, Marisa; Cejka, Anna
Abstract: Prior quantitative research with gay and bisexual men (GBM) has documented high rates of sexual risk behavior during recreational travel. Although some associations are known (e.g., substance use at the tourist destination is associated with sexual risk), less is known about GBM's motivations for travel and the cognitive and attitudinal factors that influence their sexual behavior while vacationing. In the present study, we conducted qualitative interviews with 46 GBM recruited from three popular gay tourist destinations. Using the Health Belief Model (HBM) as a guiding theoretical framework, the findings of the study revealed that the gay-friendly, tropical, relaxing environments resulted in men letting their guard down and engaging in more risk than when they are at home. Various barriers such as peer pressure and substance use affect GBM's ability to engage in healthier behaviors while traveling, with condom negotiation and HIV status disclosure as additional issues that impact the sex practices of this population. Results highlight the applicability of HBM constructs to provide insight for intervention development for this population.